The Effect of Android-Based Learning Media Using Crossword Puzzles On English Vocabulary Mastery - Rini Yudiati; Hanifatur Rizqi (IKIP Mataram, 2022)
The aim of the study were how is the application of Android-based learning media using Crossword Puzzles in learning English vocabulary for class XI students of SMKN I Sumenep, the effect and the respon of Students about crossword puzzles. This Study is a quasi-experimental with quantitative method using true experimental design for their control class and experiment. The sampel was 74 students that grouped into experimental class 38 student and control class 36 students. It is not taken randomly but chosen by the school authority. Data collection techniques used in this study is observation techniques, testing, and questionnaires. Analysis of the observation data carried out by theEnglish teachersobtained results of 92.55% at the first meeting and 94.31% at the second meeting. This is considered to have met the